Efectos de la falta de reconocimiento legítimo en el campo laboral que influyen en la identidad de un grupo de docentes de educación básica del sector privado y público. - Londoño Criollo, Lina Marcela (Universidad de San Buenaventura - Cali, 2017)
This project aimed to characterize the effects of the lack of legal recognition in the workplace that influence the identity of a group of teachers practicing in a public and private institution of basic education in the city of Santiago Cali, with it is found that both public institutions and private, teachers must be subject to the rules laid down by them, which at first may preclude the development of their autonomy, however, the bond you build with your students primarily with teachers of the public institution can give a balance to little guidance and support to be made to the teacher, the structural conditions, the demands by the parent and the education ministry feeling a motivation to give the best to them and build a multifaceted identity that strengthens the vision they have of himself and consolidates identity as a teacher, favoring the estimate by the student, a subjective construction of relationship that allows you to deal with the discomfort tha sometimes emerges from work and creating a sense, attributing a bonus and membership with the academic community especially with students.